A Practical P-Delta Analysis Method for Type FR and PR Frames - Lui, E.M. (Engineering Journal, 1988)
In the stability design of frameworks, attention must be given to the additional moment developed as a result of member and frame amplification effects from compressive axial loads. These secondary moments may have a deleterious effect on the strength and stability of the frame and so they must be reckoned with in the analysis and design processes. These are various approaches ranging from very simple to rather rigorous by which a designer can employ to account for these second-order effects. A simple and effective method of second-order frame analyses was presented in this paper. The method accounts for the P-d and P-D effects by the use of pseudo loads obtained from a first-order analysis of the frame. The method is quite versatile in that it is applicable riot only to rectangular Type FR frames but also to nonrectangular Type PR frames. The validity of the method has been demonstrated and it is therefore recommended for general use.